2022
DOI: 10.5296/rae.v14i2.19960
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration Trumps Intelligence as a Predictor of Standard of Living

Abstract: Human beings are intelligent. More importantly, they are a social species capable of cooperation. Other animals in the kingdom can cooperate. But human beings further distinguish themselves by their innate ability to collaborate. They not only take care of their children they also take care of each other. The purpose of this paper is to compare the relative impacts of collaboration and intelligence on economic growth and development. We illustrate by data and analysis, that collaboration is superior to intelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Still, collaboration and rule of law are catalysts that must prevail. As mentioned above collaboration trumps intelligence (Ridley, 2022).…”
Section: Collaboration In Governmentmentioning
confidence: 96%
See 1 more Smart Citation
“…Still, collaboration and rule of law are catalysts that must prevail. As mentioned above collaboration trumps intelligence (Ridley, 2022).…”
Section: Collaboration In Governmentmentioning
confidence: 96%
“…Ridley & de Silva (2019) showed how to evaluate the absence of collaboration and the cost of corruption. Ridley (2022) showed that collaboration is more important than intelligence for economic growth and development. Ridley, Ngnepieba & de Silva (2021) showed that collaboration in academic learning normalized calculus test scores and raised their averages.…”
Section: Related Literaturementioning
confidence: 99%